The social-psychological factors influencing women-prisoners’ feeling of loneliness - Baranauskienė, Ingrida; Kovalenko, Alla; Leonova, Inna (Social Welfare: Interdisciplinary Approach, 2020)
The article presents the study on the factors influencing appearance of loneliness at female prisoners. The results obtained indicate that loneliness is caused not only by subjective factors, such as personal traits, needs, motives, but also by an objective factor - the socially closed structure of detention places and the limited environment there. The main subjective reasons for female prisoners’ feelings of loneliness are despair, fears, depression and aggression, caused by their inability to satisfy their needs for communication, safety, personal development and goal achievement. The feeling of loneliness appears because the influence of the following factors: personal traits, insufficient interpersonal relationships, fear of rejection, subjective and objective causes